2019
DOI: 10.1039/c8ra09471c
|View full text |Cite
|
Sign up to set email alerts
|

Fish-scale-derived carbon dots as efficient fluorescent nanoprobes for detection of ferric ions

Abstract: Herein, highly fluorescent carbon dots (CDs) with the incorporation of N and O functionalities were prepared through a facile and cost-effective hydrothermal reaction using fish scales of the crucian carp as the precursor. The as-prepared CDs exhibit strong fluorescent emissions at 430 nm with a relative quantum yield of 6.9%, low cytotoxicity, and robust fluorescence stability against photobleaching and good ionic strength. More significantly, the fluorescence of these CDs can be effectively and selectively q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(37 citation statements)
references
References 65 publications
1
33
0
Order By: Relevance
“…54,55 The LOD was much lower than the Fe 3+ ions permissible level in drinking water (5.4 mM) proposed by the Environmental Protection Agency (EPA). 56 It was also comparable to the part previous reported proposed sensor for Fe 3+ ions listed in Table 1. Therefore, the CSCDs@DC for the detection of Fe 3+ ions had the superiority of wide linear ranges, low detection limit, simple operation, excellent selectivity and high sensitivity.…”
Section: Sensing Of Fe 3+ Ionssupporting
confidence: 88%
“…54,55 The LOD was much lower than the Fe 3+ ions permissible level in drinking water (5.4 mM) proposed by the Environmental Protection Agency (EPA). 56 It was also comparable to the part previous reported proposed sensor for Fe 3+ ions listed in Table 1. Therefore, the CSCDs@DC for the detection of Fe 3+ ions had the superiority of wide linear ranges, low detection limit, simple operation, excellent selectivity and high sensitivity.…”
Section: Sensing Of Fe 3+ Ionssupporting
confidence: 88%
“…Zhang et al [ 10 ], for example, reported a facile synthesis route for the preparation of CDs from grass carp scales for the detection of hypochlorite. Another work shows how fish scale-derived CDs could be used also for the determination of the presence of ferric ions in real water samples and human serum [ 31 ]. Carbon dots produced from fishery waste were synthesized also from Kai et al [ 32 ] and used for the detection of pharmaceuticals molecules as lidocaine hydrochloride.…”
Section: Introductionmentioning
confidence: 99%
“…[ 55 , 62 , 63 ]. The recent and increasing interest towards the valorization of fish scales has led to several applications in environmental protection [ 64 ], medicine [ 65 , 66 , 67 ] and bionics [ 68 ].…”
Section: Marine Collagenmentioning
confidence: 99%